Efficient approach for modeling substrate integrated waveguides. Issue 10 (2nd June 2022) - Liu, Yuanzhi; Mu, Hongyu; Yagoub, Mustapha C. E.; Bai, Guo
Abstract: In this letter, a highly accurate surrogate model of substrate integrated waveguide (SIW) is proposed. This model allows designers to design SIW structures more efficiently compared to existing complex and CPU‐intensive fine approaches. Based on the multivariate linear regression technique, an accurate equation linking the physical parameters of the proposed surrogate but simple model to the fine but complex model was obtained. The accuracy and efficiency of the proposed modeling procedure were demonstrated through a practical design example.